The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1002/1097-0142(19820815)50:4<702::aid-cncr2820500414>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of fibrolamellar oncocytic hepatoma

Abstract: The fibrolamellar variant of hepatocellular carcinoma is described and the ultrastructural findings in three cases are reported. The findings confirm the oncoytic nature of the tumor and the presence of distinctive bands of collagen. This tumor may represent a neoplasm of hepatic oncocytes. It appears to have distinct epidemiologic differences from other hepatocellular carcinomas, which typically arise in cirrhotic livers, and it may have a better prognosis. As such, it should be recognized as a distinct clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…The ultrastructural features, such as numerous mitochondria with small electron-dense deposits, dense bodies, whether membrane-bound or not, and others, correspond with previous studies (Craig et al 1980, Farhi et al 1982, An et al 1983) and explain the oncocytic, eosinophilic appearance at light microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…The ultrastructural features, such as numerous mitochondria with small electron-dense deposits, dense bodies, whether membrane-bound or not, and others, correspond with previous studies (Craig et al 1980, Farhi et al 1982, An et al 1983) and explain the oncocytic, eosinophilic appearance at light microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, tumor cells contained large nuclei with coarse chromatin and one or more prominent nucleoli (Figure 2 B and 2 C ) 19,20 , and their abundant cytoplasm was characteristically granular and eosinophilic in analogy with the “oncocyte-like” aspects of the mitochondria-rich cytoplasm in cells of human FL-HCC 21 . Indeed, ultrastructural analysis obtained by transmission electron microscopy confirmed the presence of tightly packed mitochondria in cells from mouse FL-HCC and also evidenced the characteristic nuclear morphology of these oncocytic hepatocytes 22,23 (Figure 2 D and Supplementary Figure 2 A ). Additionally, tumor cells contained inclusions resembling the intracellular “pale bodies” as well as the hyaline globules often observed in human FL-HCC (Figure 2 C , Supplementary Figure 2 B ), and accordingly, these globules contained material that was positive for the periodic acid-Schiff (PAS) stain and sensitive to diastase enzymatic digestion (Figure 2 E , and data not shown) 1 .…”
Section: Resultsmentioning
confidence: 65%
“…15 In the liver, the fibrolamellar oncocytic hepatoma, a variant of hepatocellular carcinoma, also shows densely packed, abnormal mitochondria. 16,19 These tumors need to be disassociated from the oncocytic change observed in the mitochondrial DNA depletion syndrome and in other conditions as well, such as toxicity from insecticides and valproic acid. 16 In an attempt to explain the oncocytic change, it has been suggested that such cells express high levels of oxidative and enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%